Error Estimates of Two Nonconforming Finite Elements for the Obstacle Problem (Journal of Computational Mathematics, 1986)
The linear nonconforming element and Wilson's element for the obstacle problem are considered. Optimal error bounds for both elements are obtained in the case of regular subdivisions of domain $Ω$ in $R^2$.